Pengaruh Pemberian Jus Jambu Biji Merah Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri - Anisya Oktavia Saputri; Kamidah Kamidah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: The impact of anemia in adolescents can be in the form of decreased immunity, concentration, learning achievement fitness & activity, if not properly addressed, when pregnant continues to become pregnant women with anemia, at risk of giving birth to premature babies or LBW and giving birth to the next generation of stunting which is not only short but has low intelligence (IQ), psychological disorders and is at risk of diabetes, hypertension, and other chronic diseases in the future. Prevention of anemia can be started from increasing adolescent hemoglobin levels using red guava juice which in 100 grams contains 228.3 grams of vitamin C which can help iron absorption up to 30%. Objective: to determine the effect of giving Red Guava Juice on increasing hemoglobin levels in adolescent girls. Method: using Quasi Experiment with the research design used is two group pre test- post test design. Giving Red Guava Juice with a dose of 100 grams taken 1x a day for 7 days and giving health care to the control group. The number of 30 respondents was divided into 2 groups and the data were analyzed using the Independent Sample T Test statistical test. Results: the test results showed p=0.00 <0.05 which means Ha is accepted. Conclusion: There is an effect of giving Red Guava Juice on increasing Hemoglobin levels in adolescent girls at SMA Negeri 1 Seputih Agung Lampung Tengah.